THE DIAGNOSIS AND TREATMENT OF PRIMARY PULMONARY HYPERTENSION: A MODERN VIEW ON THE PROBLEM - N. V. Porodenko; V. V. Skibitskiy; V. V. Zapevina (Кубанский научный медицинский вестник, 2014)
There are basic principles of diagnostics and treatment of patients with the primary pulmonary hypertension - Aersy desease. Clinical examples of this pathology, illustration of an echocardiology.